2015
DOI: 10.1146/annurev-physchem-040214-121713
|View full text |Cite
|
Sign up to set email alerts
|

Coherence in Energy Transfer and Photosynthesis

Abstract: Ultrafast energy transfer is used to transmit electronic excitation among the many molecules in photosynthetic antenna complexes. Recent experiments and theories have highlighted the role of coherent transfer in femtosecond studies of these proteins, suggesting the need for accurate dynamical models to capture the subtle characteristics of energy transfer mechanisms. Here we discuss how to think about coherence in light harvesting and electronic energy transfer. We review the various fundamental concepts of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
409
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 374 publications
(415 citation statements)
references
References 155 publications
6
409
0
Order By: Relevance
“…4c, d. The complexity of theory needed to predict energy transfer depends on a balance of frequency scales, as discussed in section 'Defining and detecting coherence' , necessitating development of sophisticated theories to describe details of the energy-transfer mechanism [68][69][70][71][72] . What evidence is there that these complicated theories are necessary?…”
Section: Review Researchmentioning
confidence: 99%
“…4c, d. The complexity of theory needed to predict energy transfer depends on a balance of frequency scales, as discussed in section 'Defining and detecting coherence' , necessitating development of sophisticated theories to describe details of the energy-transfer mechanism [68][69][70][71][72] . What evidence is there that these complicated theories are necessary?…”
Section: Review Researchmentioning
confidence: 99%
“…40 A highly debated point in the literature is the role of quantum mechanical coherence in the evolution of excited states in LHCs. [41][42][43] Any fluctuation of the excitonic couplings due to short range interactions coupled to thermal motion is expected to decrease the coherence and affect the exciton dynamics. 39,44,45 The aim of this paper is to evaluate the excitonic coupling between pairs of chromophores in three different LHCs and in two organic semiconductors (one amorphous and one crystalline), to achieve a broader understanding of the importance of short range interactions valid for most of the problems under current consideration.…”
Section:   a B A Bmentioning
confidence: 99%
“…16,18 A few examples in related self-assembled systems (porphyrins) have shown that exciton diffusion can efficiently occur by means of a coherent mechanism. 19 Recently, an octa(butyl)-substituted metal-free phthalocyanine, H2-OBPc (1,4,8,11,15,18,22,25-octabutoxy-29H,31H-phthalocyanine, see Figure 1a) has been synthesized and exhibited good crystallinity properties (1D π-stacked arrangements, see Figure 1b) in thin films. 20,21 The high degree of crystallinity of the solution-processed thin films allowed Rawat et al to investigate the correlation between long-range order and the nature of the lowest exciton states of the aggregate.…”
Section: Introductionmentioning
confidence: 99%